Exploring motorcycle red-light violation in response to pedestrian green signal countdown device. (February 2015) - Chen, Ping-Ling; Pai, Chih-Wei; Jou, Rong-Chang; Saleh, Wafaa; Kuo, Ming-Shin
Highlights: Drivers' and riders' red-light violation (RLV) was examined in response to pedestrian green signal countdown device. RLV and early-start behaviour appear more frequent at PGSCD intersection than a typical one. Speeds of the violating riders tend to be higher. Male/young riders, moped/large motorcycles, higher speeds, and those with tropical helmets are determents of RLV. Abstract: Literature has suggested that angle/rear-end collisions would arise from the reality that motorists and motorcyclists tended to accelerate aggressively in response to the remaining seconds of green signal countdown device (GSCD). One safety concern, while GSCD has gradually been removed for safety in Taiwan, is pedestrian green signal countdown device (PGSCD) that is used by approaching motorists and motorcyclists that may adopt the information to travel aggressively – an unintended consequence that is detrimental to safety. Research has reported that there appeared no negative effect of PGSCD on motorist behaviours but the effect on motorcyclists' behaviours has been rarely investigated. Using video/speed cameras, the current research investigates motorcyclists' RLV (red-light violation) behaviours. The descriptive analyses indicate that the percentage of RLV at PGSCD intersection is higher than that at typical intersection, and the violating motorcycles appear to have higher travelling speeds at PGSCD intersection. Several interaction terms were examined with the binary logit framework, and the results reveal that several factors are associated with RLV, notably male/young riders, moped/large motorcycle users, higher approaching speeds of motorcycles, those with tropical helmets, and lower traffic volume. Similar determinants of early-start behaviours (for those waiting at reds and could view the PGSCDs for the crossing pedestrians at the same time) were identified. Implications of the research findings, the concluding remarks, and recommendations for future research are finally provided.